Plant Feed Additives as Natural Alternatives to the Use of Synthetic Antioxidant Vitamins on Livestock Mammals' Performances, Health, and Oxidative Status: A Review of the Literature in the Last 20 Years - Carmen L. Manuelian; Rosario Pitino; Marica Simoni; Alexandros Mavrommatis; Massimo De Marchi; Federico Righi; Eleni Tsiplakou (MDPI AG, 2021)
In the last two decades, the interest in natural plant feed additives (PFA) as alternatives to synthetic vitamins in livestock nutrition has increased. After a systematic review, a total of 19 peer-reviewed papers published between 2000 and 2020 were retained to evaluate the antioxidant effects of PFA compared to synthetic antioxidant vitamins (mainly vitamin E; VitE) in livestock nutrition. These studies demonstrated that PFAs could be as efficient as VitE in counteracting oxidative stress in pigs, rabbits, and ruminants. However, PFAs only positively affected animals' growth performance and feed efficiency in some monogastric studies. The PFA can affect antioxidant enzyme activity in a dose- and method of administration-dependent manner. The antioxidant capacity of both PFA and VitE were depressed in cows fed with diets rich in polyunsaturated fatty acids. Variability among studies could be related to species differences. Despite the interest of the feed industry sector in PFA, there are still very few studies evaluating their antioxidant effect in species other than poultry.